Bacterial Superinfection of Amoebic Liver Abscess - Dhamrah, Umaima (J Investig Med High Impact Case Rep, 2020)
A 78-year-old male, originally from China, was brought to the hospital for weakness, urinary incontinence, confusion, and poor oral intake. He was started on empiric antibiotics, which were narrowed when blood cultures produced gram-negative bacteremia speciating to Klebsiella pneumoniae, sensitive to ceftriaxone. Computed tomography scan of the abdomen and pelvis demonstrated a large cystic region with air-fluid level in the left lobe of the liver. Suspecting this to be the source of the patient’s bacteremia, the lesion was percutaneously drained and the fluid cultured, which also revealed ceftriaxone-sensitive Klebsiella pneumoniae. While a stool ova and parasite examination on the patient was negative, further workup was positive for Entamoeba histolytica antibody in the serum, detected via enzyme-linked immunosorbent assay and indicative of either current or past infection. This suggested possible prolonged subclinical infection with bacterial superinfection, especially given that Klebsiella pneumoniae is one of the most common organisms cultured from these abscesses. In patients with liver abscesses who immigrated from developing and/or endemic regions or have a relevant recent travel history, an underlying amoebic etiology of an abscess should be considered.